The representation of African hair in South African dramas : a case study of Gomora, Uzalo and The River - Mabotja, Meriam (My University, 2024)
The cultural baggage and ridicule of African hair have formed part of the history of South Africa. “Good hair” has become public opinion and has consistently been defined by the beauty industry through an assortment of beauty products displayed in the media. The desire to attain “good hair” has been a life-long pursuit and this need has been designed through various avenues, which are largely displayed in the media. The mass media wield considerable influence, possessing a unique capacity to impact individuals in diverse ways. This study delves into the portrayal of African hair within the media, specifically focusing on magazines. Despite its prevalence in this medium, the research concentrates on the representation of African hair in three local South African dramas: Gomora, Uzalo, and The River. Guided by a theoretical intersection of Tajfel’s (1979) Social Identity and Hall’s (1997) Social Representation, the study aims to explore the types of hairstyles depicted in the selected dramas and the messages they convey. An exploratory research design, namely, a qualitative content-thematic analysis was employed to acquire an understanding of the representation of African hair in the selected South African dramas. The findings show that there has been a radical change in how Black women and African hair are portrayed and represented in South African dramas. Black women are portrayed as powerful and play the role of protagonist and antagonist in all the three dramas. Natural hairstyles are most dominant, specifically the afro, which is associated with power and leadership. This shift in the representation of African hair and Black women is significant for South African media
Thesis (M. A. (Media Studies)) -- University of Limpopo, 2023
Keywords: African hair; Dramas; Artificial hairstyles; Natural hairstyles; Hair; Afro (Hairstyles); Hairstyles -- South Africa